Pembelajaran Tahfidz Al-Qur`An dalam Membentuk Karakter Islami - M.Erwinsyah Nasution; Idris Siregar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Education is a crucial aspect of human life, including the teaching of the Qur'an, which is considered a noble act of worship in Islam. The process of Qur'anic memorization (Tahfidz) at Rumah Tahfiz Mata Air Dakwah Jalan Pendidikan Bandar Khalifah is part of the Islamic education curriculum aimed at developing Islamic character in students. However, the implementation and effectiveness of the Tahfidz program often face challenges in learning management and memorization reinforcement. This research employs a qualitative approach using observation, interviews, and documentation methods. Data were collected through direct observation, interviews with administrators and teachers, and analysis of documents related to the Tahfidz program. Data analysis followed the stages of reduction, presentation, and verification, as guided by Miles and Huberman. The study found that Qur'anic memorization education at Rumah Tahfiz Mata Air Dakwah has made significant progress due to effective leadership and implemented policy strategies. Teaching methods such as Tasmi' and Muroja'ah have proven effective in enhancing students' memorization quality. The integration of Tahsin Qiraah lessons into the curriculum also positively contributes to reading and memorization skills. Additionally, the cultivation of Islamic character is well-implemented through various activities supporting religious values, discipline, and cleanliness. Observations indicate that the percentage of students successfully memorizing the Qur'an has significantly increased over the past three years.